Squamous cell carcinoma initially arising in the midline of the dorsum of the tongue in a young adult: A case report and review of the literature. Issue 3 (May 2019) - Toh, Taketomo; Akita, Takako; Saito, Masaki; Shigetomi, Toshio
Abstract: Squamous cell carcinoma (SCC) of the tongue typically affects individuals over 50 year of age, is relatively rare in patients who are less than 40, and occurs most often on the lateral borders. SCC of the dorsum of the tongue is relatively rare and reported to comprise only 2.9%–7.2% of all cases, and SCC in the midline of the tongue dorsum accounts for less than 1% of tongue carcinoma. We report an exceedingly rare case of SCC of the tongue arising in the midline of the dorsum in a 33-year-old man and review the literature. The patient was referred by a primary care physician and visited our hospital with a chief complaint of a mass in the midline of the tongue dorsum. Intraoral examination revealed a mass with a diameter of 14 × 13 mm anterior to the vallate papillae in the midline of the dorsum of the tongue. The mass was ellipse, well-circumscribed and elastic hard with no surrounding induration. There was no palpable enlarged lymph in the submandibular and cervical region. An incision biopsy was performed under local anesthesia. The pathological diagnosis was well-differentiated SCC. Based on a clinical diagnosis of tongue carcinoma T1N0M0, a partial glossectomy setting 10 mm or more safety margin around the tumor was performed under general anesthesia in June 2015. The postoperative course was uneventful, therefore, the patient was discharged on the 10th postoperative day. During follow-up for 3 years, there has been no dysfunction such as dysphagia and dysarthria, and no sign of recurrence or metastasis.